A historical and systematic survey of European perceptions of wilderness - Kirchhoff, Thomas; Vicenzotti, Vera (Environmental values, 2014)
This paper develops a historical and systematic typology of perceptions of wilderness that exist in contemporary western European cultures. After describing notions of wilderness associated with worldviews that emerged during the Enlightenment period (theological, early Enlightenment, liberalism, democratism) and as a critical response to it (Rousseauism, early Romanticism, English and German conservatism), we outline four recent transformations of these traditional notions of wilderness: wilderness as an ecological object, as a place of nature's self-reassertion, as a place of thrill and as a sphere of amorality and meaninglessness. In our conclusion, we suggest what practical relevance arises from such a nuanced understanding of the inherently ambiguous concept of wilderness.
Gesehen am 25.01.2021